2021
DOI: 10.1098/rspb.2021.0545
|View full text |Cite
|
Sign up to set email alerts
|

Out of the extratropics: the evolution of the latitudinal diversity gradient of Cenozoic marine plankton

Abstract: Many ecological and evolutionary hypotheses have been proposed to explain the latitudinal diversity gradient, i.e. the increase in species richness from the poles to the tropics. Among the evolutionary hypotheses, the ‘out of the tropics’ (OTT) hypothesis has received considerable attention. The OTT posits that the tropics are both a cradle and source of biodiversity for extratropical regions. To test the generality of the OTT hypothesis, we explored the spatial biodiversity dynamics of unicellular marine plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 53 publications
1
8
0
Order By: Relevance
“…The DES framework is not limited to analyses of vertebrates at continental scales or the terrestrial realm (e.g. Carrillo et al, 2020), but can also inform on changes in micro‐organism diversity through regional dispersal and local extinction (Wilke et al, 2020) or across oceans (Raja & Kiessling, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The DES framework is not limited to analyses of vertebrates at continental scales or the terrestrial realm (e.g. Carrillo et al, 2020), but can also inform on changes in micro‐organism diversity through regional dispersal and local extinction (Wilke et al, 2020) or across oceans (Raja & Kiessling, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Carnivora, dispersal, diversity dependence, extinction, fossil biogeography, paleoenvironment, PyRate, trait-dependent biogeography Previous studies using the DES model interpreted temporal variation in dispersal and extinction rates as the impact of biotic or abiotic factors on these rates. For instance, these studies suggested that the formation of the Isthmus of Panama enabled the interchange of mammal genera between the Americas (Carrillo et al, 2020), that an increase in competition among diatom species caused a decrease in the rate of lake colonization (Wilke et al, 2020) and that warmer time intervals facilitated the dispersal of marine plankton from the extratropics into the tropics (Raja & Kiessling, 2021). Due to methodological limitations, these interpretations were based on comparing the temporal rate trajectories with climate or diversity curves instead of directly inferring the influence of these curves on dispersal and extinction rates.…”
Section: Introductionmentioning
confidence: 99%
“…There may in fact be two distinct, contrasting phases to the evolution of the modern LDG through the Cenozoic era. The mass extinction event at the Cretaceous-Paleogene (K-Pg) boundary was followed by a global pulse of diversification that persisted for c. 25 Myr (Crame, 2020;Harvey et al, 2020;Raja & Kiessling, 2021). Although regional LDGs are not yet available for the Early Cenozoic, all the indications are that this pulse was much more intense in the tropics than at the poles; relatively steep LDGs almost certainly existed at this time (Crame, 2020).…”
Section: Is There a L Atitud Inal G R Ad Ient In R Ate S Of Ori G Ina...mentioning
confidence: 99%
“…Their shape has quantitatively useful parameters which can establish the origin of a species [11] or be used to investigate changes in climate impacts on evolution [12]. Quantitatively, the field of foraminiferal micropaleontology is testing in earnest the influences of geography on dispersal and evolution [e.g., [13][14][15]. Within taxonomy, the community has come together to produce consensus atlases [e.g., 16] and individuals have produced a Cenozoic lineage phylogeny at the species level reflecting that taxonomic consensus [17], even quantifying identification error [18].…”
Section: Introductionmentioning
confidence: 99%